A Trauma-Informed Approach to Youth Suicide Prevention and Intervention. Issue 3 (3rd July 2021) - Tunno, Angela M.; Inscoe, Adrienne Banny; Goldston, David B.; Asarnow, Joan Rosenbaum
ABSTRACT: Suicide, suicidal behaviors, and self-harm are major public health problems among youth and can often co-occur with traumatic stress experiences and related symptoms. Given this interrelation, it is important that suicide prevention and intervention practices take a trauma-informed approach to reflect the complex, intertwined relation of traumatic stress symptoms and suicidal thoughts/behaviors. To that end, we summarize key steps in a proposed trauma-informed approach to suicide prevention and illustrate this approach with examples of how to clinically apply suggested components for youth who are suicidal and have been exposed to traumatic events.